Protective Mechanism of Unburned Pulverized Coal to Coke in Blast Furnace (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The edge and internal morphology of coke with different contents of UPC (unburned pulverized coal) after reaction with CO2 were analyzed by SEM. The influence of UPC on CRI (coke reactivity)，CSR (coke strength after reaction) and apparent porosity was also studied. The synthetic weighted mark method was used to analyze the comprehensive effect of UPC content on coke quality. The results show that because the decrease of the content of intermediates Cf(O) and C(O)Cf(O), so the restrictive step between the coke and CO2 is interfacial chemical reaction, and it accords with the Mckewan equation 1-(1-α)1/3=kt. The UPC has a strong effect on coke when the content of UPC is 10~20%, meanwhile , the CRI and apparent porosity are significantly decreased by 6.8% and 9.5% respectively, and the CSR is significantly increased by 3.8%. The UPC can effectively reduce the effect of CO2 on the edge and internal erosion of coke, the large pores and pulverization of coke were avoided. The results of synthetic weighted mark method shown that the comprehensive quality of coke changed greatly when the content of unburned pulverized coal is 11.24~20.87%, which is agreement with the experimental results.